"[...] was the best prime minister" - the image and activities of José Zapatero as the former Prime Minister of Spain = "[...] najlepszy były premier" - wizerunek i działalność José Zapatero po zakończeniu sprawowania funkcji premiera Hiszpanii - Podedworna, Daria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is dedicated to the image of the former Prime Minister of Spain, J.L. Rodriguez Zapatero aQer the two-term rule of the socialist Partido Obrero Espa?ol in December 2011. An attempt was made to check what happens to the politician, and more precisely to his image, at the end of a political career. Is this, at the moment, possible to change the political image?
Keywords: Zapatero, José Luis Rodríguez (1960- ); former prime minister; political image; Spanish political scene; wizerunek polityczny; hiszpańska scena polityczna